1996
DOI: 10.1182/blood.v88.8.3065.bloodjournal8883065
|View full text |Cite
|
Sign up to set email alerts
|

Two types of defective human T-lymphotropic virus type I provirus in adult T-cell leukemia

Abstract: Adult T-cell leukemia (ATL), an aggressive neoplasm of mature helper T cells, is etiologically linked with human T lymphotropic virus type I (HTLV-1). After infection, HTLV-I randomly integrates its provirus into chromosomal DNA. Since ATL is the clonal proliferation of HTLV-I-infected T lymphocytes, molecular methods facilitate the detection of clonal integration of HTLV-I provirus in ATL cells. Using Southern blot analyses and long polymerase chain reaction (PCR) we examined HTLV-I provirus in 72 cases of AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
126
0
3

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(137 citation statements)
references
References 32 publications
8
126
0
3
Order By: Relevance
“…However, we cannot exclude the possibility that polyubiquitination may have nothing to do with NF-κB activation because the introduced mutations could alter the conformation of Tax rendering it inactive. Many proviruses in ATL cells isolated from patients lack 5′-long-terminal repeat (LTR), (58) or maintain LTR but heavily methylated. (59) Therefore, Tax cannot be expressed in leukemic cells although NF-κB is usually constitutively activated.…”
Section: Nf-κ κ κ κB In Adult T-cell Leukemiamentioning
confidence: 99%
“…However, we cannot exclude the possibility that polyubiquitination may have nothing to do with NF-κB activation because the introduced mutations could alter the conformation of Tax rendering it inactive. Many proviruses in ATL cells isolated from patients lack 5′-long-terminal repeat (LTR), (58) or maintain LTR but heavily methylated. (59) Therefore, Tax cannot be expressed in leukemic cells although NF-κB is usually constitutively activated.…”
Section: Nf-κ κ κ κB In Adult T-cell Leukemiamentioning
confidence: 99%
“…Inverse polymerase chain reaction (inverse PCR). To amplify the genomic DNA flanking the integration sites of the HTLV-I provirus, inverse PCR was performed using a previously described method 15) with some modification. Genomic DNA (500 ng) was digested with PstI (Toyobo, Osaka) and then ligated with T4-DNA ligase (New England Biolabs, Beverly, MA).…”
Section: Methodsmentioning
confidence: 99%
“…Schemas of the structure of complete, Type 1 defective and Type 2 defective HTLV-1 provirus are shown in Figure 1. 16 The nucleotide position number of HTLV-1 provirus was according to Seiki et al (accession no. J02029).…”
Section: Quantification Of Htlv-1 Provirus In Pbmcsmentioning
confidence: 99%
“…5,13 It has been reported that defective provirus was detectable in approximately half of patients with ATL. [14][15][16][17][18] Tamiya et al reported two types of genome deletion in defective provirus. 16 One form (i.e., Type 1) retains both LTRs and lacks internal sequences, such as the gag and pol regions.…”
mentioning
confidence: 99%
See 1 more Smart Citation